2007
DOI: 10.1016/j.bbapap.2007.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Hemocyanin conformational changes associated with SDS-induced phenol oxidase activation

Abstract: The enzymatic activity of phenoloxidase is assayed routinely in the presence of SDS. Similar assay conditions elicit phenoloxidase activity in another type 3 copper protein, namely hemocyanin, which normally functions as an oxygen carrier. The nature of the conformational changes induced in type 3 copper proteins by the denaturant SDS is unknown. This comparative study demonstrates that arthropod hemocyanins can be converted from being an oxygen carrier to a form which exhibits phenoloxidase activity by incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 57 publications
(44 reference statements)
6
53
0
2
Order By: Relevance
“…Dodecamer is required for agglutination of Litopenaeus vannamei hemocyanin with bacterial cells and red blood cells [31]. Baird et al reported that the micellar form of SDS is required to induce optimal conformational transitions in hemocyanin, which may result in eliciting phenoloxidase activity [32]. Garcia-Carreno et al indicated that activation of hemocyanin to phenoloxidase by endogenous (serine proteinases) and exogenous (SDS) effectors needs complex aggregation for displaying enzyme activity [33].…”
Section: Discussionmentioning
confidence: 98%
“…Dodecamer is required for agglutination of Litopenaeus vannamei hemocyanin with bacterial cells and red blood cells [31]. Baird et al reported that the micellar form of SDS is required to induce optimal conformational transitions in hemocyanin, which may result in eliciting phenoloxidase activity [32]. Garcia-Carreno et al indicated that activation of hemocyanin to phenoloxidase by endogenous (serine proteinases) and exogenous (SDS) effectors needs complex aggregation for displaying enzyme activity [33].…”
Section: Discussionmentioning
confidence: 98%
“…Therein, multiple metal ion binding modes for this structure were described through a cooperative model describing high copper ion plasticity controlling reactivity and substrate selectivity of the active site coppers is thought to limit CO to diphenolase activity and Hc to reversible oxygen binding. In support of copper ion plasticity and sampling between different enzyme forms, the reversible oxygen binding with Hc was altered through the addition of a denaturant (SDS) that moved blocking residues opening the active site to the catalytic oxidation of the diphenolic substrate dopamine while CO has copper coordinating histidine residues positioned in a conformationally labile loop regions [60, 61]. Based on our molecular modeling studies, the proposed binding orientations for 2-aminophenol and catechol are essentially superimposable with respect to benzene ring positioning near H296 and proximity to the CuA – CuB binding domains for both E met and E oxy forms of abTy (Figures 6 and 7).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a detailed study on arthropod Hc conformational changes associated with SDS-induced PO activation was reported [14]. It was shown that the micellar form of SDS (present at concentrations >1 mM in 100 mM sodium phosphate buffer, pH 7.5) is required to induce optimal conformational transitions in the protein, which may result in opening a channel to the di-copper centre allowing bulky phenolic substrates to access the catalytic site.…”
Section: Induction Of Phenoloxidase Activity By Sdsmentioning
confidence: 99%
“…The kinetic parameters [K M (mM), V max (nmol min −1 mg −1 ) and k cat (min −1 ; expressed per copper pair)] were derived from non-linear regression data analysis of the dependence of the initial rates on the substrate concentration using HYPER software, taking into account the molar absorption coefficient of o-quinone 1417 M −1 cm −1 [11] or of dopachrome 3600 M −1 cm −1 [14] and the molecular mass of a FU (entity with one active site; 50 kDa).…”
Section: Assay Of Phenoloxidase Activitymentioning
confidence: 99%
See 1 more Smart Citation